Factores psicosociales de la deserción escolar de jóvenes wayuu en una institución del municipio de Uribía La Guajira (2024)
The main objective of this next research project is to describe the psychosocial factors related to school dropout of Wayuu youth in an Ethno-educational institution in Uribia La Guajira, taking into account the academic performance of the students of said institution under study, taking as a reference theoretical models such as Tinto's, which is one of the common ones, including variables such as academic, family and emotional factors. For the development of the research, a quantitative study was carried out, which in turn has a non-experimental design with a descriptive scope with a sample of 71 students of which 38 were female and 33 were male who are between 14 and 20 years old. In order to collect data and statistical analysis, a School Dropout scale questionnaire was applied through the SPSS program. This instrument evaluates the academic, family and emotional dimensions